Synthesis, properties and applications of self‐repairing carbohydrates as smart materials via thermally reversible DA bonds. (2nd November 2020) - Guo, Ming; Chen, Lei; Fang, Tao; Wang, Rui; Nuraje, Nurxat; Brodelius, Peter E.
Abstract : Self‐healing carbohydrate polymers were synthesized by Diels‐Alder reaction. Intermediate products and the carbohydrate matrices were characterized by Fourier transform infrared spectroscopy (FT‐IR) and 1 H NMR, while the thermally reversible properties were assessed by FT‐IR and differential scanning calorimetry. The mechanical properties, water absorption, and enzymatic degradation of starch/PVA/modified carbohydrate films were examined, as well as the relationship of the properties to the DA and rDA reactions. These results showed that DA bonds were introduced into the carbohydrate polymers successfully and endow the material with self‐healing thermal recyclability. The mixed films exhibited alternating strong and weak mechanical properties upon cycling through the DA and rDA reactions. Water absorption was limited and the films demonstrated good water resistance. The status of the DA bonds was found not to affect the enzymatic degradation rates of the various carbohydrate films.